Facile synthesis of B/N co-doped 2D porous carbon nanosheets derived from ammonium humate for supercapacitor electrodes. (1st March 2019) - Geng, Qianhao; Huang, Guangxu; Liu, Yingbin; Li, Yuanyuan; Liu, Longhui; Yang, Xiaohui; Wang, Qi; Zhang, Chuanxiang
Abstract: In this work, we report a facile method for preparing the B/N co-doped 2D porous carbon nanosheets (BNHCs) with high contents of boron (3.41–3.96 at.%) and nitrogen (5.1–6.09 at.%) via annealing the mixtures of ammonium humate and H3 BO3 . The ammonium humate is used as nitrogen-containing carbon precursor, and H3 BO3 acts as boron source and pore-forming agent. Moreover, we demonstrate firstly that the existence of H3 BO3 can enhance the graphitization degree of BNHCs by inducing the conversion of BCO2 to BC3 with increasing the H3 BO3 /ammonium humate mass ratio to 2. BNHC-1.5 exhibits the highest specific surface area of 592 m 2  g −1 among all the samples, and BNHC-2 shows the enhanced graphitization degree and highest mesopore ratio (60.5%). In a three-electrode system, the BNHC-1, BNHC-1.5 and BNHC-2 exhibit high specific capacitances of 305 F g −1, 311 F g −1 and 225 F g −1 at 0.2 A g −1, and 64 F g −1, 125 F g −1 and 120 F g −1 at ultrahigh current density of 100 A g −1, respectively. Moreover, as assembled symmetric supercapacitor electrodes with high active material mass loading (∼180 μm, ∼13 mg cm −2 ), BNHCs deliver high specific capacitances of 170–210 F g −1 at 0.05 A g −1, and BNHC-2 presents an outstanding cyclic stability (94.8% capacitance retention after 10, 000 cycles), making them promising candidates for practical supercapacitor application. Graphical abstract: Highlights: ∙ B/N co-doped 2D porous carbon nanosheets (BNHCs) with high contents of boron (3.96 at.%) and nitrogen (6.09 at.%) are prepared by one-step carbonization of the mixtures of ammonium humate and H3 BO3 . ∙ The conversion of BCO2 to BC3 species can be induced via increasing the additive amount of H3 BO3 even at relatively low temperature of 900 °C. ∙ The BNHCs supercapacitor electrodes exhibit high gravimetric capacitance, outstanding rate capability and cyclic stability with high mass loading (∼ 180 μm, ∼ 13 mg cm -2 ).